Review of the Oriental lantern-fly genus Egregia Chew Kea Foo, Porion & Audibert, 2011, with a new species from Sumatra (Hemiptera: Fulgoromorpha: Fulgoridae) - Jérôme Constant (European Journal of Taxonomy, 2014)
Datua brevirostris Lallemand, 1959 is transferred to the genus Egregia Chew Kea Foo, Porion & Audibert, 2011 in the Aphaeninae and the new combination Egregia brevirostris (Lallemand, 1959) comb. nov. is proposed. Egregia marpessa Chew Kea Foo, Porion & Audibert, 2011, the type-species of the genus Egregia, is synonymized with Egregia brevirostris (Lallemand, 1959). A second species, Egregia laprincesse sp. nov. is described from Sumatra, extending the distribution of the genus hitherto recorded only from Borneo. Distribution maps and an identification key are provided. The male genitalia of E. brevirostris are illustrated and described. The genus Datua Schmidt, 1911 now contains a single species, D. bisinuata Schmidt, 1911.